JURIDIC ANALYSIS OF FISHERY CRIMINAL ACTIONS TO REALIZE THE SOVEREIGNTY OF THE NATION AND THE STATE (Research Study at Batam Marine and Fishery Resources Supervision Base Office) - Setiadi, Kotot; Idham, Idham; Parameshwara, Parameshwara; Fadllan, Fadllan; Erniyanti, Erniyanti; Ramlam, Ramlam (RADJA PUBLIKA, 2022)
In Indonesia, there are many illegal economic problems, but one of the most detrimental to the state is the problem of Illegal, Unregulated, and Unreported Fishing Practices (IUU Fishing) by foreign ships. IUU Fishing is defined as illegal fishing activities, not reported to the authorized fisheries management institution, and fishery activities that have not been regulated in existing regulations. So the role of law enforcement is very important to tackle acts of lawlessness in Indonesian waters. The form of law enforcement is to implement government policies by applying criminal sanctions in the form of fines, confinement, confiscation/confiscation of evidence and sinking foreign ships that steal fish in Indonesian waters. Article 8 of Law no. 45 of 2009 concerning Fisheries states